Gender-specific genetic and epigenetic signatures in cardiovascular disease - Bridges, Justin; Ramirez-Guerrero, Jose A.; Rosa-Garrido, Manuel (Frontiers in Cardiovascular Medicine, 2024)
Cardiac sex differences represent a pertinent focus in pursuit of the long-awaited goal of personalized medicine. Despite evident disparities in the onset and progression of cardiac pathology between sexes, historical oversight has led to the neglect of gender-specific considerations in the treatment of patients. This oversight is attributed to a predominant focus on male samples and a lack of sex-based segregation in patient studies. Recognizing these sex differences is not only relevant to the treatment of cisgender individuals; it also holds paramount importance in addressing the healthcare needs of transgender patients, a demographic that is increasingly prominent in contemporary society. In response to these challenges, various agencies, including the National Institutes of Health, have actively directed their efforts toward advancing our comprehension of this phenomenon. Epigenetics has proven to play a crucial role in understanding sex differences in both healthy and disease states within the heart. This review presents a comprehensive overview of the physiological distinctions between males and females during the development of various cardiac pathologies, specifically focusing on unraveling the genetic and epigenetic mechanisms at play. Current findings related to distinct sex-chromosome compositions, the emergence of gender-biased genetic variations, and variations in hormonal profiles between sexes are highlighted. Additionally, the roles of DNA methylation, histone marks, and chromatin structure in mediating pathological sex differences are explored. To inspire further investigation into this crucial subject, we have conducted global analyses of various epigenetic features, leveraging data previously generated by the ENCODE project.